Preparation of Polyvinyl Alcohol from Local Raw Material - K. Haweel, Cecelia; H. Ammar, Saad (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Polyvinyl alcohol, (PVA) was prepared using polyvinyl acetate emulsion (manufactured by Al-Jihad factory,That-Al-Sawary Company) as a local raw material. In this investigation, polyvinyl acetate emulsion was converted tosolid form by coagulation the polymer from its emulsion using sodium sulphate salt as coagulant aid, then alcoholyzedthe solid polyvinyl acetate in methanol using sodium hydroxide as catalyst, polyvinyl alcohol produced by this method isa dry, white to yellow powder.Three affecting variables on the degree of hydrolysis of PVA were studied, these variable are Catalyst topolymer weight ratio in the range of 0.01 – 0.06, reaction time in the range of 20 – 90 min, and reaction temperature inthe range of 25 – 50 oC. The effect of degree of hydrolysis of PVA produced on its properties such as water solubilityand degree of polymerization were studied also.Finally the alcoholysis reaction kinetics were studied to determine the reaction constants such as initial rateconstant and degree of autocatalytic effect of the alcoholysis reaction. It was found that the degree of hydrolysis offormed polyvinyl alcohol increase with increasing of variables catalyst concentration, reaction time and reactiontemperature, furthermore, the water solubility of PVA increase with increasing degree of hydrolysis up to about 87 %after this value the solubility is decrease, also the degree of polymerization of PVA decrease with increasing of degree ofhydrolysis up to about 89 %.